Detection of Streptococcus pyogenes from Throat Swab in Acute Pharyngitis Patients - Maulana, Ibnu Tsabit; Megantara, Imam; Husen, Ike Rostikawati (Althea Medical Journal, 2016)
Background: Pharyngitis is an inflammation of throat that may be caused by viral and bacteria. Although Streptococcus pyogenes is only responsible for 5â15% of cases of pharyngitis in adults. Antibiotics are highly prescribed for this infection, thus it could lead to antibiotic resistance. The main reason for antibiotic overprescription is the difficulty to obtain a rapid and correct etiological diagnosis. This study aimed to determine the frequency of Streptococcus pyogenes from throat swab in patient with acute pharyngitis in Padjadjaran Clinic.Methods: This study was a descriptive study. Specimen was taken from the patients in Padjadjaran Clinic on September until October 2014. Thirty-five patients with acute pharyngitis that met the selection criteria were recruited for throat swab. Then, specimens obtained were performed an identification testing to determine whether there was a colonization of Streptococcus pyogenes. Results: Thirty five patients were found with acute pharyngitis consist of 14 male and 21 female, with age ranged between 16â34 years old. From the identification testing result, Streptococcus pyogenes was not found from throat swabs of patient with acute pharyngitis in Padjadjaran Clinic.Conclusions: This study found no colonization of Steptococcus pyogenes in throat swabs of acute pharyngitis patients in Padjadjaran Clinic, however Streptococcus pyogenes was not the causative fact of acute pharyngitis. [AMJ.2016;3(1):69â72]Â DOI:Â 10.15850/amj.v3n1.716